Pengembangan Koleksi di Perpustakaan Universitas Panca Bhakti - Pajar Julhijah (UIN Mataram, 2022)
Collection development is a tool for identifying the needs of the library. The needs in question are not onlypresent needs but cover the next 5 years. In addition, the development of the collection covers the needs of thelibrary as a whole, not only the needs of active users. Thus, this research describes the Development ofCollections in the Panca Bhakti University Library. This research uses qualitative methods with data collectiontechniques using interview and observation techniques. The results of this study are several processes carriedout by the Panca Bhakti University Library including: 1. Survey of Library Needs of The Library, 2. Concept ofCollection Development, 3. Poses Collection Procurement, 4. Weeding Collection, 5. Evaluation of Activities